The Implementation of the Merdeka Curriculum and Its Implications for the Internalization of Anti-Corruption Values Among Students - Ni Luh Wayan Yasmiati; I Wayan Lasmawan; I Gusti Putu Suharta; I Wayan Widiana (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2026)
This study aims to analyze the implementation of the Merdeka Curriculum and its implications for the internalization of anti-corruption values among students in public junior high schools (SMPN) in Singaraja City. The research employed a descriptive qualitative approach, with data collected through in-depth interviews with teachers involved in implementing the Merdeka Curriculum at SMP Negeri 2 and SMP Negeri 4 Singaraja. The findings indicate that implementing the Merdeka Curriculum has positive implications for the internalization of anti-corruption values, particularly through project-based learning and the Pancasila Student Profile Strengthening Project (Proek Penguatan Profil Pelajar Pancasila/P5), which facilitates the contextual cultivation of values such as honesty, responsibility, and integrity. The curriculum's flexibility allows teachers to design character education that is relevant to students’ learning experiences. However, these implications have not yet been fully optimized due to several constraints, including limited operational guidelines for anti-corruption education, insufficient teacher training, and uneven understanding among students and educators regarding the substance of anti-corruption values. In addition, institutional support from schools and family involvement in reinforcing value-based practices remain suboptimal. This study recommends strengthening collaborative strategies among schools, local governments, and the community to ensure the sustainable internalization of anti-corruption values within the Merdeka Curriculum framework. This research contributes to the development of contextual character education practices and provides insights for the formulation of anti-corruption education policies at the school level.